2016
DOI: 10.1007/s11250-016-1049-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of FAMACHA in estimation of gastrointestinal nematodes and total worm burden in Damara and Barbados Blackbelly cross sheep

Abstract: The prevalence of gastrointestinal (GI) nematodes and total worm burden of Damara and Barbados Blackbelly cross sheep was investigated among smallholder farms in Salak Tinggi district of Selangor, Malaysia. A total of 50 sheep raised in smallholder farms comprising of 27 Damara cross and 23 Barbados Blackbelly cross were categorized based on their age into young and adults. Fecal samples were collected and examined for strongyle egg count by using modified McMaster technique. Severity of infection was categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
4
17
0
2
Order By: Relevance
“…In small ruminants, gastrointestinal nematodes (GINs) infections represent important challenges in the tropical and subtropical regions [ 5 , 6 ]. Infections with GIN affect the welfare of the animals and cause huge economic losses in livestock farming [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In small ruminants, gastrointestinal nematodes (GINs) infections represent important challenges in the tropical and subtropical regions [ 5 , 6 ]. Infections with GIN affect the welfare of the animals and cause huge economic losses in livestock farming [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common GINs that affect small ruminants are Haemonchus , Trichostrongylus , Ostertagia , Cooperia , Bunostomum , Oesophagostomum , Chabertia , and Nematodirus [ 8 ]. There are potential threats associated with economic losses through lowered productivity, reduced animal performance and weight gain, retarded growth, a cost of treatment, and mortality [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of different strategies on control of gastrointestinal nematodes (FAMACHA © system, clinical signs, body condition score and fecal egg count) was beneficial with evaluated in different sheep categories (Mohammed et al 2016), showing a different response intra-herd, but a high ability of the animals against GIN (Molento 2009). Also, an early identification of high percentage of anemic animals, with high fecal egg count, lower PCV and TPP could represent an early therapeutic approach within the modern concept of targeted selective treatments (O'Shaughnessy et al 2015) with a subsequent strategic and economic benefit (Di Loria et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To better parasitic control and to reduce the use of anthelmintic some strategies have been proposed: biological control (Waller 2006), cooper oxide needles (Vatta et al 2009), medicinal plants (Sawleha et al 2010), vaccination (Arunkumar et al 2012) and the use of targeted selective treatments (TST) (Kenyon & Jackson 2012, O'Shaughnessy et al 2015, Mohammed et al 2016. As per of our knowledge, one of the cutting-edge resources used to slow down the development of anthelmintic resistance is the FAMACHA © system, a selective method useful for controlling gastrointestinal verminosis in small ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…A number of functional genomics studies have indicated that the Damara does have an unique fatty acid metabolism [32]. In comparison to the Barbados blackbelly sheep in Malaysia, the Damara exhibited lower gastro-intestinal infection [33]. Tolerance to seasonal weight loss, which is an important adaptation trait during seasonal droughts, was exhibited by the Damara and Dorper breeds in relation to the Australian Merino [34,35].…”
Section: Phenotypic Characterisation and Traits Important For Selectionmentioning
confidence: 98%